The Role of Bank Reputation in “Certifying” Future Performance Implications of Borrowers’ Accounting Numbers - BUSHMAN, ROBERT M.; WITTENBERG‐MOERMAN, REGINA (Journal of Accounting Research, 2012)
ABSTRACT We investigate the role played by the reputation of lead arrangers of syndicated loans in mitigating information asymmetries between borrowers and lenders. We hypothesize that syndications by more reputable arrangers are indicative of higher borrower quality at loan inception and more rigorous monitoring during the term of the loan. We investigate whether borrowers with more reputable lead arrangers realize superior performance subsequent to loan origination relative to borrowers with less reputable arrangers. We further examine whether certification by high‐reputation lead banks extends to the quality of borrowers’ reported accounting numbers. Controlling for endogenous matching of borrowers and lead banks, we find that higher bank reputation is associated with higher profitability and credit quality in the three years subsequent to loan initiation. We also show that bank reputation is associated with long‐run sustainability of earnings via higher earnings persistence, and debt contracting value of accounting via a stronger connection between pre‐loan profitability and future credit quality. We further document that the enhanced earnings sustainability associated with higher reputation lead banks reflects both superior fundamentals and accruals more closely linked with future cash flows.